Management of avulsion wound in a calf: a case report - Sadiq, Muhammad Abubakar; Abdullah, Faez Firdaus Jesse; Tijjani, Abdulnasir; Mohammed, Konto; Abba, Yusuf; Lim, Eric Teik Chung; Adamu, Lawan; Osman, Abdinasir Yusuf; Mohd Lila, Mohd Azmi; Haron, Abd Wahid; Saharee, Abdul Aziz (International Organization of Scientific Research, 2015)
A male Jersey calf weighing 50kg was presented to the University Veterinary Hospital, University Putra Malaysia with an open non-bleeding contaminated wound situated at the caudo-lateral aspect of carpal joint of the left forelimb. The calf was apparently stable and alert and on examination there was extensive damage to the skin around the wound area. Based on the physical examination and history, the case was diagnosed as that of an avulsed wound. The affected area was cleaned, debrided and lavaged with 0.05% diluted chlohexidine diacetate and Ilium Dermapred®. It was then bandaged after spraying with woundsarex spary; a fly repellant/antiseptic spray. Positive response of the calf to the treatment was noticed within two weeks of treatment. Daily wound dressing, debridement and topical antibiotic treatment was adequate in treatment of non-infected avulsion wound. In order to prevent the occurrence of such type of injuries, it is recommended that farmers should keep animal premises clear of injurious materials such as wire fences, metal sheets, or other sharp objects and stray dogs. Young animals should be segregated from adults to protect them from physical injuries.